Numerical simulation of the de-bonding phenomenon of FRCM strengthening systems - Ernesto Grande; Maura Imbimbo; Sonia Marfia; Elio Sacco (Fracture and Structural Integrity)
Aim of the paper is to present a one dimensional simple model for the study of the bond behavior of Fabric Reinforced Cementitious Matrix (FRCM) strengthening systems externally applied to structural substrates. The equilibrium of an infinitesimal portion of the reinforcement and the mortar layers composing the strengthening systems allows to derive the governing equations. An analytical solution is determined solving the system of differential equations. In particular, in the first part of the paper a nonlinear shear-stress slip law characterized by a brittle post-peak behavior with a residual shear strength in the post peak phase is introduced for either the lower reinforcement-mortar interface (approach 1) or both the lower and the upper interface (approach 2). In the latter approach, a calibration of the shear strength of the upper interface is proposed in order to implicitly account for the effect of the damage of the mortar on the bond behavior. In the second part of the paper it is presented the solution of the problem in the case of softening behavior by approximating the shear-stress slip law throughout a step function. Comparisons with experimental data, available in literature, are presented in order to assess the reliability of the proposed approach.